Investigation of Physical and Mechanical Properties for Interlocking Paver Block from Foam Waste Binder - Napia, Chuwit; Saengthong, Chiaewchan; In-aram, Warayut; Srisuwan, Anuwat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This study investigates the feasibility of producing interlocking paver blocks using a mixture of sand and dissolved foam binder at varying contents ranging from 10 to 50 wt%. The results indicate that paver blocks could be successfully formed without edge fractures when the foam binder content was within the range of 20 - 40 wt%. As the foam content increased, the samples exhibited improved densification, while porosity and water absorption significantly decreased due to the infiltration of foam into the micropores. Consequently, the compressive strength of the paver blocks improved with higher foam content, reaching a maximum at 40 wt% foam binder. These findings confirm that interlocking paver blocks produced with 20 - 40 wt% foam binder meet the required strength standards, demonstrating the potential of foam waste as an effective alternative binder in sustainable construction applications.